Perlindungan Hukum Terhadap Hak Atas Layanan Administrasi Kependudukan Pada Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Karangasem - Sugita, I Made (Metta : Jurnal Ilmu Multidisiplin, 2022)
Population administration services will play a strategic role in providing protection as well as recognition of the personal status of residents before the law, whether in the form of a person's status, name, address and so on. On this basis, it is necessary to apply the principles of good service law in population administration services so that people get protection for their rights. This study aims to identify and analyze the implementation of the legal principles of good public service and legal protection of the right to population administration services at the Department of Population and Civil Registration of Karangasem Regency. The type of research used in compiling this research is empirical legal research. This research is descriptive-qualitative in nature. The type of data used is in addition to using primary data also using secondary data. Primary data collection techniques through field research, while secondary data obtained through library research. The results of the study show that: first, that the Karangasem Regency Population and Civil Registration Office has not fully complied with the legal principles of good public service, particularly the principles of openness, participation and accountability. This can be seen from the lack of application of adequate service standards, the low level of knowledge of public service staff which has implications for the accuracy and discipline of service staff, the unavailability of supporting facilities and infrastructure and the low level of public understanding of the importance of population documents. Second, Legal protection of community rights in the field of population administration services at the Karangasem Regency Population and Civil Registration Service as mandated in the provisions of Article 2 of Law Number 24 of 2013 concerning Amendments to Law Number 23 of 2006 concerning Population Administration has not been fully implemented as should be in accordance with the corridor that has been determined. The community's rights that are not implemented properly are actually obliged to get legal protection, in fact this has not received a good response and a settlement pattern that benefits the community.